The Effectiveness of Using Quiz Bot as an Online Learning Method - Asroriyah, Atik Muhimatun; Maskuroh, Siti; Amanah, Firma Pradesta (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
The COVID-19 pandemic has significantly altered the educational landscape. Distance learning, which used to be carried out face-to-face, needs attractive and simple-to-use learning resources for both teachers and students. Telegram is a platform that is simple to use and has a lot of benefits. Mastery and use of technology to support successful learning has become a necessity and is increasingly educative, especially during the COVID-19 pandemic. Teachers as the main actors in driving educational progress are required to keep up with the times and be creative in the use of media in the form of a Learning Management System (LMS). Therefore, this article aims to explain about the provision of the use of Telegram Quiz Bot as a means of teaching English material, especially structure material. The use of this media is carried out by Telegram users with high school age who have an interest in learning English on Telegram. This study used a descriptive qualitative approach. Data obtained from active Telegram users with the results of each structure question given 45 seconds of time with the results obtained from 20 participants, 3 people 90% correct, 7 people 50% correct and the remaining 30%. This is because Quiz bot has several more benefits as a medium for learning listening material, namely providing a means of making multiple choice questions, polling features, quiz descriptions, text and images. In addition, the quiz bot is easy to use and there is an audit facility in it.Keyword : Quiz Bot, Learning Management System (LMS), Structure